2017
DOI: 10.1007/s10741-017-9617-4
|View full text |Cite
|
Sign up to set email alerts
|

DPP4 inhibitors and cardiovascular outcomes: safety on heart failure

Abstract: Diabetes is an important risk factor for cardiovascular disease. However, clinical data suggests intensive glycemic control significantly increase rather than decrease cardiovascular mortality, which is largely due to the fact that a majority of oral anti-diabetic drugs have adverse cardiovascular effect. There are several large scale clinical trials evaluating the cardiovascular safety of DPP4 inhibitors, a novel class of oral anti-diabetic medications, have been recently completed. They were proven to be saf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
15
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(16 citation statements)
references
References 50 publications
0
15
0
Order By: Relevance
“…There is also a direct effect on calcium transport and lipid metabolism, leading to diabetic cardiomyopathy. Sympathetic over-expression in heart failure is responsible for increased insulin resistance, reduces insulin secretion and stimulates glucagon release, which induces hepatic gluconeogenesis (6).…”
Section: Mechanism Of Action Of Glp-1 Hormone and Its Pleiotropic Effmentioning
confidence: 99%
“…There is also a direct effect on calcium transport and lipid metabolism, leading to diabetic cardiomyopathy. Sympathetic over-expression in heart failure is responsible for increased insulin resistance, reduces insulin secretion and stimulates glucagon release, which induces hepatic gluconeogenesis (6).…”
Section: Mechanism Of Action Of Glp-1 Hormone and Its Pleiotropic Effmentioning
confidence: 99%
“…The Saxagliptin Assessment of Vascular Outcomes Recorded in Patients with Diabetes Mellitus-Thrombolysis in Myocardial Infarction 53 (SAVOR-TIMI 53) trial [8], the Examination of Cardiovascular Outcomes With Alogliptin Versus Standard of Care (EXAMINE) [9] trial, and the Trial Evaluating Cardiovascular Outcomes with Sitagliptin (TECOS) [10] demonstrated that, compared with placebo, the addition of saxagliptin, alogliptin and sitagliptin, respectively, neither increased nor decreased the event rate for the primary composite endpoint ( baseline risk for CV events. In SAVOR-TIMI 53 [8], the addition of saxagliptin to existing therapy had a neutral effect on individual components of the primary composite endpoint versus placebo; however, this treatment was associated with a significantly increased risk of HF-related hospital admissions.Consequently, the effect of DPP-4 inhibitors on HF risk in patients with T2DM has been further evaluated in patients with T2DM, and trials of alogliptin, sitagliptin, and vildagliptin did not demonstrate similar results [11]. CVOTs have also been conducted with the selective DPP-4 inhibitor, linagliptin, to further examine its efficacy and safety in high-risk populations.…”
Section: History Of Conditionmentioning
confidence: 99%
“…Dipeptidyl peptidase-4 (DPP-4) inhibition is a promising oral treatment for T2D either as monotherapy or in combination with other antidiabetic agents. 10,11 This inhibition results in increased insulin secretion and reduced glucagon production by preventing the inactivation of glucose-dependent insulinotropic polypeptide glucagon-like peptide-1 (GLP-1), the two main incretin hormones. 12 Numerous clinical studies have demonstrated that incretin-based therapies are superior to traditional oral hypoglycaemic agents in terms of clinical efficacy and tolerability.…”
Section: Introductionmentioning
confidence: 99%